2009
DOI: 10.1111/j.1365-2044.2009.06075.x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the GlideScope® for tracheal intubation in patients with cervical spine immobilisation by a semi‐rigid collar

Abstract: SummaryApplication of cervical collars may reduce cervical spine movements but render tracheal intubation with a standard laryngoscope difficult if not impossible. We hypothesised that despite the presence of a Philadelphia Patriot® cervical collar and with the patient’s head taped to the trolley, tracheal intubation would be possible in 50 adult patients using the GlideScope® and its dedicated stylet. Laryngoscopy was attempted using a Macintosh laryngoscope with a size 4 blade, and the modified Cormack–Lehan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
47
1
3

Year Published

2013
2013
2016
2016

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(54 citation statements)
references
References 28 publications
3
47
1
3
Order By: Relevance
“…We needed maneuvers in 15% of patients in the ILMA group. Our study and other studies demonstrated that GlideScope needed 21% maneuver application in difficult airways (11,26).…”
Section: Discussionsupporting
confidence: 70%
See 3 more Smart Citations
“…We needed maneuvers in 15% of patients in the ILMA group. Our study and other studies demonstrated that GlideScope needed 21% maneuver application in difficult airways (11,26).…”
Section: Discussionsupporting
confidence: 70%
“…A study reported longer insertion and intubation times than our findings with ILMA under MAILS and collar immobilization (17,21). However, previously immobilized patients were intubated for similar durations as we did in our study by GlideScope (11,15).…”
Section: Discussionsupporting
confidence: 63%
See 2 more Smart Citations
“…They are useful devices for understanding the airway anatomy and tracheal intubation procedure. Moreover, their superiority to the Macintosh laryngoscopy in tongue oedema and cervical trauma victims has been validated (1)(2)(3)(4)(5)(6).…”
Section: Introductionmentioning
confidence: 99%